History of Problem Based Learning in Nepal and Experiences at Kathmandu Medical College - Pradhan, B; Ranjit, E; Ghimire, MR; Dixit, Y (Journal of Kathmandu Medical College, 2012)
Problem Based Learning has been practised in Nepal for 30 years with some additional inputs every ten years as another medical institution of Nepal adopted it. The institution to introduce it in Nepal was the Institute of Medicine but its practise there is more as familiarisation about a method of learning medicine and making a diagnosis. As from 2012 the utilisation of Problem Based Learning in the MBBS medical education field is expected to increase as the two deemed and two full universities in Nepal are using this method to varying degrees. There are firm advocates for utilising PBL in the medical colleges of Nepal. There are many who would like to stick to the traditional methods saying that PBL is not in extensive use. The fact is that the traditional form of medical education and the PBL method have their positive and negative points and is the source of much debate. We in Nepal have not gone the full stretch with PBL. What we are practising here is mostly the hybrid form. DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7255 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.37-44